(untitled) (JOSAR (Journal of Students Academic Research), 2025)
The COVID-19 pandemic has significantly impacted financial stability across industries, including the aviation sector. PT Angkasa Pura I (Persero) and PT Angkasa Pura II (Persero) have faced increased debt levels, necessitating an analysis of leverage risk in their financial performance. This study aims to assess the companies’ leverage conditions and identify potential risk mitigation strategies using Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) as analytical tools. A qualitative descriptive approach is employed, utilizing secondary data from 2017 to 2020. The analysis focuses on examining financial reports and relevant literature to understand the extent of leverage risk and its implications. The findings indicate that both companies exhibit high debt levels, placing them in an unhealthy financial state. This condition could lead to financial distress, limiting operational flexibility and increasing vulnerability to external economic shocks. Furthermore, the results suggest that excessive leverage poses significant risks, making it difficult for the companies to secure further funding from creditors or attract potential investors. To mitigate this issue, it is recommended that PT Angkasa Pura I and PT Angkasa Pura II explore alternative financial sources, such as increased equity financing through shareholders and investors or issuing new shares. Additionally, restructuring existing debt and optimizing cost management strategies could help improve financial resilience. This study highlights the critical need for effective debt management strategies to enhance financial sustainability and investor confidence. The insights from this research contribute to the broader understanding of leverage risk management in the aviation sector, especially in times of economic downturns and global crises.